Quality Assesment of Social Public Services - Nicolina Racoceanu; Aniela Matei; Bertha Sanduleasa; Mihaela Ghenta (Amfiteatru Economic Journal, 2009)
The article investigates a less approached domain in the theoretical papers and in the research field, namely the quality of social public services. In the first part we present some characteristics of social public services and their importance within the public budget construction and for the local communities. Starting from the identified characteristics we made a research focused on quality assessment in social public services. The initial step was made considering the processes administration approach, because an efficient administration leads to an increased efficiency, efficacy and finally to a better quality. The basic assumption is that, within the assessment process, assessing the quality for the supplier is essential. Moreover, quality should be related to process and to organizational structure from which it derives. The research covers the Public Services of Social Assistance (PSSA's), the selection of investigation units was made by the three administrative-territorial levels and using the questionnaire as data collecting technique. Data interpretation was made both for regions and areas of residence, using techniques of descriptive statistical analysis. The results reveal significant quality differences between regions and also between areas of residence, concerning the following issues: organisational structure, human resources, the existence of a social services developing plan, partnerships concluded with civil society organisations, social needs uncovered and barriers to access to social public services.
Keywords: H83; L38; 330; social public services; public administration; organizational management; quality assessment; assessment methodology